Research of integral parameters for furnaces of a circulating fluidized bed; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 82 : Thermophysical Basis of Energy Technologies - Gil A. V. Andrey Vladimirovich (2015, 2015)
Title screen